2021
DOI: 10.1158/1078-0432.ccr-20-2487
|View full text |Cite
|
Sign up to set email alerts
|

A Pan-Histone Deacetylase Inhibitor Enhances the Antitumor Activity of B7-H3–Specific CAR T Cells in Solid Tumors

Abstract: Purpose: The limited efficacy of chimeric antigen receptor (CAR) T-cell therapies with solid malignancies prompted us to test whether epigenetic therapy could enhance the antitumor activity of B7-H3.CAR T cells with several solid cancer types.Experimental Design: We evaluated B7-H3 expression in many human solid cancer and normal tissue samples. The efficacy of the combinatorial therapy with B7-H3.CAR T cells and the deacetylase inhibitor SAHA with several solid cancer types and the potential underlying mechan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 53 publications
(68 reference statements)
0
19
0
Order By: Relevance
“…Recently, NK-cells have been used to generate CAR-NK cells, which controlled the growth of human NSCLC cells grafted in murine models and prolonged survival (95). Lei et al reported that a pan-histone deacetylase inhibitor can enhance the antitumor activity of B7-H3-specific CAR T cells in solid tumors (96).…”
Section: Targeting B7-h3 With Chimeric Antigen Receptor T Cells and Chimeric Antigen Receptor Nk Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, NK-cells have been used to generate CAR-NK cells, which controlled the growth of human NSCLC cells grafted in murine models and prolonged survival (95). Lei et al reported that a pan-histone deacetylase inhibitor can enhance the antitumor activity of B7-H3-specific CAR T cells in solid tumors (96).…”
Section: Targeting B7-h3 With Chimeric Antigen Receptor T Cells and Chimeric Antigen Receptor Nk Cellsmentioning
confidence: 99%
“…Lei et al. reported that a pan-histone deacetylase inhibitor can enhance the antitumor activity of B7-H3-specific CAR T cells in solid tumors ( 96 ).…”
Section: B7-h3-based Tumor Immunotherapy Strategiesmentioning
confidence: 99%
“…For instance, anti-HER2 CAR-T augmented with anti-PD-1 monoclonal antibody presented potent cytotoxicity, and thus regressed tumor growth in the trastuzumab-resistant breast cancer cell lines [ 191 ]. A deacetylase inhibitor SAHA administered with CAR-T recognizing B7-H3, an immune checkpoint, increased the expression of the target molecule at the transcriptional level and decreased the expression of CTLA-4 and TET2, a methylcytosine hydroxylating enzyme, on effector cells [ 192 ].…”
Section: Strategies To Overcome Immunotherapy Resistance Of Breast Cancermentioning
confidence: 99%
“…Of note, our results have distinguished that B7-H3, also known as CD276, might be a promising therapeutic target for CAR-based therapy, and there is evidence that it carries no risk of on-target off-tumor toxicity ( 57 , 58 ). Recently, our research team also found that SAHA, a pan histone deacetylase inhibitor, could enhance B7-H3.CAR-T cells in solid tumors ( 59 ). Elsewhere, novel approaches have been investigated to overcome biological barriers in solid tumors, for example, using local delivery systems; applying anti-vasculature agents, chemokines or oncolytic viruses; and equipping effector immune cells with the ability to generate chemokines or heparinase to degrade the extracellular matrix ( 60 ).…”
Section: Discussionmentioning
confidence: 98%